Effectiveness and Safety of Bleomycin Sclerotherapy in Pediatric Low-Flow Vascular Malformations: A Retrospective Cross-Sectional Study - Rio Hermawan; Koesbandono Koesbandono; Raditya Utomo; Hardini Intan S. Mahdi; Ade Nurlina; Ratna Sari Wijaya (Medicinus, 2026)
Background: Low-flow vascular malformations (LFVMs) are congenital vascular anomalies commonly managed using sclerotherapy. Among available sclerosant agents, bleomycin has demonstrated favorable therapeutic efficacy and safety profiles in pediatric vascular malformations, although treatment responses remain variable across different lesion types and morphologies.   Methods: This retrospective cross-sectional study evaluated pediatric patients with LFVMs who underwent bleomycin sclerotherapy at Dharmais Cancer Hospital between January 2019 and May 2025. Demographic characteristics, lesion profiles, treatment sessions, cumulative bleomycin doses, therapeutic outcomes, and treatment-related adverse events were analyzed. Therapeutic responses were categorized into Grade 0-3 outcomes.   Result: A total of 41 pediatric patients with LFVMs were included in the study. Patients aged 0-5 years represented the largest age group (51.2%), while the head and neck region was the most common lesion location (41.4%). Venolymphatic malformations (51.2%) and microcystic lesions (65.8%) were the predominant lesion subtypes. Grade 2 clinical response was the most frequently observed therapeutic outcome (58.5%), whereas Grade 3 response was identified in 17.1% of patients. The mean number of treatment sessions was 5.80 +/- 2.42. Treatment-related adverse events were minimal, with pain and edema observed in one patient each (2.4%), and no cases of pulmonary injury or major systemic complications identified. No significant association was found between treatment sessions or cumulative bleomycin dose and therapeutic outcomes (p>0.05).   Conclusions: Bleomycin sclerotherapy demonstrated favorable effectiveness and safety profiles in pediatric patients with LFVMs. Therapeutic outcomes appeared to be influenced more strongly by lesion characteristics than by treatment intensity or cumulative bleomycin dose.